Nomina zoologica linnaeana* - Dubois, Alain (Zootaxa, 2007)
A complete survey of the classification of the animal kingdom in Linnaeus (1758)’s tenth edition of the Systema Naturae shows that 5222 taxa were recognized and diagnosed in this book. Some of these taxa were diagnosed in the text, and some in tables which clearly show the hierarchical relationships between taxa according to Linnaeus. Most of the taxa (4735, i.e., 90.7 %) were referred to four primary key ranks (classis, ordo, genus, species) and these were all named. The remaining 487 taxa were distributed among 12 optional ranks (from “subregnum” to “infravarietas”), and only 215 of them (44.1 %) were named. Most of these nomina (173, i.e. 80.5 %) are of “subgeneric” and “infrasubgeneric” ranks above species, and they are unavailable in zoological nomenclature, having being invalidated by Opinion 124 of the International Commission on Zoological Nomenclature. However, thirteen “subgeneric” nomina were “revalidated” and are still in use in zoology. Besides, five nomina for taxa above the rank genus and 31 for taxa below the rank species, although ignored by many zoologists until now, are nomenclaturally available. This unconventional analysis shows that the idea of having a complex hierarchy of ranks, some of which are “mandatory”, whereas the others are optional and can be used if the need appears, is as old as the “Linnaean” system itself. It also stresses the difference between taxonomy and nomenclature, which is sometimes misunderstood: it is fully possible to discover, recognize and diagnose a taxon without naming it, and this has been so since the Systema Naturae.